Correlates of Implicit Cognitive Line Length Representation in Two-Dimensional Space. Issue 2 (October 2014) - Doty, Richard L.; Koti, Ajay; Landy, Jeffrey; Shin, Christina; O'Hara, Thomas A.; Silas, Jonathan
Twenty-eight sex- and age-matched participants, half dextrals and half sinstrals, were instructed to move a pen-sized planometer three inches (7.6 cm) while blindfolded. Under separate trials, movements were made at four angles, towards and away from the body, and at two distances from the body (30 cm, 53 cm). Half were made with the right hand and half with the left hand. Line estimates increased in length across blocks of trials in a linear fashion and progressively overestimated the three-inch imagined criterion. Lines made moving towards the body were longer than those made moving away from the body, implying an egocentric frame of reference in making the estimates. Line estimates made at an oblique angle differed significantly from estimates made at other angles. No influences of sex, handedness, or the hand used in making the estimates were observed. The findings suggest that motoric estimates of line lengths made without visual cues—a unique measure of an implicit cognitive concept—are significantly altered by temporal and spatial factors, but not by sex or hemispheric laterality.